Synthesis of PVP-coated nanoparticles based on ferrum oxide - Yermekova, A.; Tulebayeva, D. (The 6th International Conference on Nanomaterials and Advanced Energy Storage Systems. Institute of Batteries LLP, Nazarbayev University, and PI “National Laboratory Astana”., 2018)
Magnetic nanoparticles, especial Fe3O4, are the most interesting particles among others because of their attractive properties and a wide range of application in various areas. But magnetic nanoparticles have huge surface energy and strong magnetic interactions between particles, which lead them to be more affected by uncontrollable aggregation in normal conditions of preparation. Stabilization could be achieved by electrostatic and steric repulsion. Particles coating by ionic compounds increase electrostatic repulsion, when two particles approach, that provide more effective stabilization.
Keywords: nanoparticles; Magnetic nanoparticles